Endocrine Regulation in the Ovary by MicroRNA during the Estrous Cycle - Toms, Derek; Pan, Bo; Li, Julang (Frontiers in Endocrinology, 2018)
Hormonal control of the estrous cycle that occurs in therian mammals is essential for the production of a functional egg. Supporting somatic cell types found within the ovary, such as granulosa and theca cells respond to endocrine signals to support oocyte maturation and ovulation. Following the release of the egg, now available for fertilization, coordinated hormonal signaling between the mother and putative embryo are required for the establishment of pregnancy. If no conception occurs, both the ovary and uterus are ‘reset’ in preparation for another cycle. The complex molecular changes that occur within cells in response to hormone signaling include a network of non-coding microRNAs that post-transcriptionally regulate gene expression. They are thus able to fine-tune cellular responses to hormones and confer robustness in gene regulation. In this review, we outline the important roles established for microRNAs in regulating female reproductive hormone signaling during estrus, with a particular focus on signaling pathways in the ovary. Understanding this microRNA network can provide important insights to improving assisted reproductive technologies and may be useful in the diagnosis of female reproductive disorders.